Modification of Tio2/ZrO2 catalyst by fluorination and alkylsilylation - 193481 Izan Izwan Misnon; Halimaton Hamdan, supervisor; Fakulti SAins (2005)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2005